Recent Results on Nonlinear Delay Control Systems In honor of Miroslav Krstic - Karafyllis, Iasson; Malisoff, Michael; Mazenc, Frederic; Pierdomenico, Pepe (Advances in Delays and Dynamics, 2016)
This volume collects recent advances in nonlinear delay systems, with an emphasis on constructive generalized Lyapunov and predictive approaches that certify stability properties. The book is written by experts in the field and includes two chapters by Miroslav Krstic, to whom this volume is dedicated. This volume is suitable for all researchers in mathematics and engineering who deal with nonlinear delay control problems and students who would like to understand the current state of the art in the control of nonlinear delay systems.